OPTIMALISASI KUALITAS AIR DI KOBER DAARUL AMAL MENGGUNAKAN SISTEM FILTRASI UNTUK MENINGKATKAN SANITASI LINGKUNGAN DAN KESEHATAN ANAK - Sofia, Evi; Septianissa, Selly; Suryaman, Nia Nuraeni; Komarudin, Udin; Martoni, Martoni; Chandrasari, Ayu Zahra; Prasetia, Adhita; Zanika, Sugih Yusuf; Nugraha, Suhud; Trisnawan , Lukman (Universitas Mataram, 2025)
Daarul Amal Playgroup (KOBER), an early childhood education establishment situated in Bandung City, plays a pivotal role in fostering an intelligent and healthy generation. Nonetheless, despite its significant role in educating children, this institution encounters some obstacles, particularly with the quality of water utilized in everyday operations. This community service initiative seeks to enhance water quality at KOBER Daarul Amal by instructing students on the significance of clean water and implementing a filtration system utilizing three filter media: zeolite, ferrolite, and activated charcoal. The outcomes of the educational initiatives for students indicated an increased awareness regarding the significance of clean water. The outcomes of educational initiatives indicate that students have increased their awareness regarding the significance of clean water. Furthermore, the implementation of water filtration has enhanced the water quality at the site, as demonstrated by the initial TDS test results, which ranged from 455.3 ppm to 359,7 ppm, and the turbidity value, which decreased from 4.50 NTU to 4.48 NTU. In addition, based on the results of the questionnaire given to the teachers, it can also be concluded that this community service activity has met its targets.